Seção Técnica de Materiais - Bini, Alexandro Roberto; Ossune, Anny Kellen; Araújo, Ari Alves de; Lourenço, Leonardo; Santos, Magali Aparecida dos; Borges, Marco Antônio Morais; Silva, Solange Pedroso da; Splendor, Tânia Mara; Sanches, Viviane Ribeiro (ARCHIVES OF HEALTH INVESTIGATION, 2013)
Apresentação - Alexandro Roberto Bini